1150 A Painless Anterior Chest Wall Mass Post Coronary Artery Bypass Grafting Surgery. (12th October 2021) - Reid, R; Alakhras Aljanadi, F; Beattie, R; Graham, A
Abstract: Aim: We aim to present here a case of a painless anterior chest wall mass which was first noted during routine follow up post coronary artery bypass graft surgery Case presentation: An 80-year-old male developed an asymptomatic slow growing pronounced swelling over the right anterior chest wall post CABG. His other past medical history includes chronic obstructive pulmonary disease, pulmonary fibrosis, ischaemic heart disease, an AICD for complete heart block, hypertension, hyperlipidaemia and osteoarthritis. A CT scan demonstrated a 10 x 12 x 6.5 cm subcutaneous lesion at the mid-line of the lower chest wall adjacent to the xiphisternum and the previous sternotomy site. On clinical examination there was a large non-tender cystic swelling with peripheral calcifications, but overlying skin was normal. Fluid was aspirated from the lesion and cytology showed a paucicellular specimen with features in keeping with seroma. Due to the progressive increase in size patient underwent surgical resection. A gelatinous bloody fluid was aspirated from the lesion and it was then resected enbloc. The tumour base appeared to arise from 6/7th costal cartilage and tumour was shaved away. The mass was confirmed histologically to be chondrosarcoma. Conclusions: Given the uncommon prevalence of malignant primary chest wall tumours this case highlights the importance of high clinical suspicion even after developing post CABG.